Analysis of toxicity and mechanisms of busulfan in non-obstructive azoospermia: A genomic and toxicological approach integrating molecular docking, single-cell sequencing, and experimentation in vivo - Yanggang Hong; Qichao Yuan; Yi Wang; Deqi Wang; Xiaoju Guan; Congde Chen (Ecotoxicology and Environmental Safety)
Environmental pollutants, including chemical contaminants, heavy metals, and pesticides, have been linked to adverse effects on male reproductive health, particularly sperm quality. Non-obstructive azoospermia (NOA) is a severe form of male infertility caused by intrinsic testicular dysfunction, leading to a complete absence of sperm in the ejaculate. Busulfan, an alkylating chemotherapeutic agent widely used to treat chronic myelogenous leukemia, is known to induce NOA through its toxic effects on spermatogonial stem cells (SSCs). This study aimed to identify key molecular targets and pathways disrupted by busulfan in the testicular environment. By integrating molecular docking, single-cell RNA sequencing, and in vivo experimentation, the study identified POLE and LRAT as critical proteins. These proteins were shown to interact strongly with busulfan, leading to genomic instability and increased germ cell apoptosis during spermatogenesis. Additionally, the immune landscape of NOA-affected testes revealed significant changes in immune cell infiltration, potentially worsening the condition. These findings offer new insights into the mechanisms of busulfan-induced NOA and suggest potential therapeutic targets for preserving male fertility in chemotherapy patients. This research advances the understanding of chemotherapy-induced reproductive toxicity and emphasizes the need for strategies to reduce its negative effects on fertility.